Interferon-α and thymosin-α1 plus tislelizumab enhance CD8+ T cell cytotoxicity toward pancreatic ductal adenocarcinoma - Shun Deng; Rilin Deng; Jinfeng Wang; Qi Hu; Biaoming Xu; Jinhai Zheng; Mingjing Peng; Wenzhi Tan; Haizhen Zhu; Chaohui Zuo (iScience)
Summary: The strong immunosuppression and immune evasion of pancreatic ductal adenocarcinoma (PDAC) result in poor efficacy of immune checkpoint blockade. In this study, the PD-1 level on CD8+ T cells in the peripheral blood of patients with PDAC was significantly greater than that in the peripheral blood of healthy individuals. To enhance the anticancer activity of adoptive CD8+ T cells toward PDAC, interferon-α (IFN-α) and thymosin-α1 (Tα1) plus tislelizumab were preclinically explored. Compared with those of tislelizumab monotherapy, the proliferation and cytokine secretion of CD8+ T cells and the cytotoxic activity toward PDAC cells were significantly greater with the combination treatment of IFN-α and Tα1 plus tislelizumab. Moreover, the growth of PDAC tumors was inhibited by CD8+ T cells with high efficacy under the combination treatment. Thus, IFN-α and Tα1 plus tislelizumab enhance the anticancer activity of CD8+ T cells toward PDAC, representing an alternative strategy for improving cancer immunotherapy.